Measurement of CP violation in B0 → D+D − and B s 0 $$ B_{s}^0 $$ → D s + D s − $$ D_{s}^{+}{D}_{s}^{-} $$ decays - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract A time-dependent, flavour-tagged measurement of CP violation is performed with B 0 → D + D − and B s 0 $$ {B}_s^0 $$ → D s + D s − $$ {D}_s^{+}{D}_s^{-} $$ decays, using data collected by the LHCb detector in proton-proton collisions at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 6 fb −1. In B 0 → D + D − decays the CP-violation parameters are measured to be S D + D − = − 0.552 ± 0.100 stat ± 0.010 syst , C D + D − = 0.128 ± 0.103 stat ± 0.010 syst . $$ {\displaystyle \begin{array}{c}{S}_{D^{+}{D}^{-}}=-0.552\pm 0.100\left(\textrm{stat}\right)\pm 0.010\left(\textrm{syst}\right),\\ {}{C}_{D^{+}{D}^{-}}=0.128\pm 0.103\left(\textrm{stat}\right)\pm 0.010\left(\textrm{syst}\right).\end{array}} $$ In B s 0 $$ {B}_s^0 $$ → D s + D s − $$ {D}_s^{+}{D}_s^{-} $$ decays the CP-violating parameter formulation in terms of ϕ s and |λ| results in ϕ s = − 0.086 ± 0.106 stat ± 0.028 syst rad , ∣ λ D s + D s − ∣ = 1.145 ± 0.126 stat ± 0.031 syst . $$ {\displaystyle \begin{array}{c}{\phi}_s=-0.086\pm 0.106\left(\textrm{stat}\right)\pm 0.028\left(\textrm{syst}\right)\textrm{rad},\\ {}\mid {\lambda}_{D_s^{+}{D}_s^{-}}\mid =1.145\pm 0.126\left(\textrm{stat}\right)\pm 0.031\left(\textrm{syst}\right).\end{array}} $$ These results represent the most precise single measurement of the CP-violation parameters in their respective channels. For the first time in a single measurement, CP symmetry is observed to be violated in B 0 → D + D − decays with a significance exceeding six standard deviations.